I'd know you anywhere - Lippman, Laura, 1959- (New York : William Morrow, 2011)
Eliza Benedict's peaceful suburban life is shattered after she is contacted by Walter Bowman, the man who kidnapped and held her hostage as a teen in 1985, and who now claims to want forgiveness while on death row.
Keywords: Kidnapping victims -- Fiction; Psychological fiction; Suspense fiction